Design Of 0.18-µm CMOS Voltage Controlled Oscillator (VCO) For 2.45ghz IOT Application - Tan, Hui Wen (Universiti Sains Malaysia, 2018)
Smart spaces is promoted as an antecedent to an Internet of Things (IoT) due to rapid growth of miniaturization of electronics and its integration into daily products. One of the challenging RF front ends blocks for IoT are the design of low phase noise and low power circuit. There is a necessity to raise the performance of transceiver to tackle this challenge. The voltage-controlled oscillator (VCO) represents the vital block to determine an RF transceiver performance. Hence, the design will be emphasized on low power VCO. In CMOS VCO design in this research, the typical topology implemented is the LC-tank VCO. However, to achieve the same performance as an LC-tank VCO at lower power consumption, a current reuse CMOS VCO was implemented. The current reuse class-C VCO has higher DC-RF current conversion efficiency and in overall more superior in performance than the class-B VCO. In this work, a 0.18-um current reuse class-C VCO consuming low power has been implemented for use in 2.45 GHz Internet of Things (IoT) applications. The power consumption and phase noise are 1.99 mW and -110.0 dBc/Hz@1MHz respectively. At the end of this work, the performance achieved by the current reuse class-C VCO will be compared with work by others in the same area.